Current state of immune checkpoints therapy for glioblastoma - He Wang; Jing Yang; Xiangjun Li; Hai Zhao (Heliyon, 2024)
Glioblastoma (GBM), one of the most aggressive forms of brain cancer, has limited treatment options. Recent years have witnessed the remarkable success of checkpoint inhibitor immunotherapy across various cancer types. Against this backdrop, several clinical trials investigating checkpoint inhibitors for GBM are underway in multiple countries. Furthermore, the integration of immunotherapy with traditional treatment approaches is now emerging as a highly promising strategy. This review summarizes the latest advancements in checkpoint inhibitor immunotherapy for GBM treatment. We provide a concise yet comprehensive overview of current GBM immunotherapy options. Additionally, this review underscores combination strategies and potential biomarkers for predicting response and resistance in GBM immunotherapies.